2015
DOI: 10.1016/j.jnci.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolated skeletal muscle metastatic deposit in a patient with micropapillary carcinoma thyroid identified by 18F FDG PET CT

Abstract: Micropapillary carcinoma of thyroid is said to be low risk differentiated thyroid malignancy with excellent prognosis. We report the identification of an isolated FDG avid muscle deposit in a treated case of micropapillary carcinoma of the right lobe and widely invasive follicular carcinoma of the left lobe thyroid gland. Patient was found to have an elevated thyroglobulin level with negative iodine scan (TENIS syndrome) on follow up at 6 months. An 18F FDG PET CT (18 fluorine-fluorodeoxyglucose positron emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…A case of PTC presenting as a solitary metastasis in the right arm muscle in an elderly hyperthyroid male patient was mentioned by Pucci et al [18]. Similar to our study, the only case of papillary microcarcinoma skeletal metastasis found in the literature, is presented by Sarma et al, considering a 66 years old male left deltoid metastasis found on an FDG-PET/CT scan, after negative 131-iodine WBS while thyroglobulin level was 123.2 ng/mL [7]. Zhao et al reported the case of rectus abdominis muscle metastasis from PTC identified by I-131 SPECT/CT as an incidental focus of abnormally increased I-131 uptake [20].…”
Section: The Available Evidence Of the Existing Casessupporting
confidence: 88%
See 2 more Smart Citations
“…A case of PTC presenting as a solitary metastasis in the right arm muscle in an elderly hyperthyroid male patient was mentioned by Pucci et al [18]. Similar to our study, the only case of papillary microcarcinoma skeletal metastasis found in the literature, is presented by Sarma et al, considering a 66 years old male left deltoid metastasis found on an FDG-PET/CT scan, after negative 131-iodine WBS while thyroglobulin level was 123.2 ng/mL [7]. Zhao et al reported the case of rectus abdominis muscle metastasis from PTC identified by I-131 SPECT/CT as an incidental focus of abnormally increased I-131 uptake [20].…”
Section: The Available Evidence Of the Existing Casessupporting
confidence: 88%
“…The most common skeletal metastasis site appears to be the erector spinae [14][15][16]19] and thigh muscle group [10][11][12][13]. Unique cases of muscle metastasis sites were reported localized in trapezoid [17], arm biceps [18], deltoid [7], gastrocnemius [9], and rectus abdominis [20] muscles. In summary, to the best of our knowledge, this is the second reported case of distant solitary skeletal metastasis from papillary thyroid microcarcinoma.…”
Section: The Available Evidence Of the Existing Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common muscle involved in PTC/FTC malignancy was the gluteus muscle, as observed in 16% of reported cases, compared with the erector spinae muscles as concluded by other modern papers ( 8 , 10 , 17 ). The present review of the literature identified just 4 cases of erector spinae DTC metastasis (7%).…”
Section: Discussionmentioning
confidence: 58%
“…In 2015, Portela et al ( 16 ) presented a case of PTC muscle metastasis within the sternocleidomastoid muscle and reviewed the literature, identifying just 1 previous case of PTC muscle metastasis. Sarma et al ( 17 ) described a case of FTC deltoid muscle metastasis; from reviewing the literature, the authors reported just 3 cases of solitary DTC muscle metastases. Cassidy et al ( 18 ) reported a case of PTC muscle metastasis; they reported 3 documented cases of symptomatic PTC muscle metastasis, and 3 cases of incidentally diagnosed PTC by single-photon emission computed tomography/CT and PET/CT, from the literature.…”
Section: Resultsmentioning
confidence: 99%